2022
DOI: 10.3389/fimmu.2022.972184
|View full text |Cite
|
Sign up to set email alerts
|

BAG6 negatively regulates the RLR signaling pathway by targeting VISA/MAVS

Abstract: The virus-induced signaling adaptor protein VISA (also known as MAVS, ISP-1, Cardif) is a critical adaptor protein in the innate immune response to RNA virus infection. Upon viral infection, VISA self-aggregates to form a sizeable prion-like complex and recruits downstream signal components for signal transduction. Here, we discover that BAG6 (BCL2-associated athanogene 6, formerly BAT3 or Scythe) is an essential negative regulator in the RIG-I-like receptor signaling pathway. BAG6 inhibits the aggregation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“… 30 , 31 Furthermore, BAG6 could suppress RNA virus‐mediated innate immunity by increasing VISA/TRAF2 K48 poly‐ubiquitination. 32 Clearly, the upregulation of BAG6 greatly promoted BCL2 ubiquitination in MDA‐MB‐231 cells (Figure 6F ). A GST pull‐down assay in vitro was performed using the purified GST‐BAG6 and GST‐BCL2 proteins generated in E. coli BL21.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“… 30 , 31 Furthermore, BAG6 could suppress RNA virus‐mediated innate immunity by increasing VISA/TRAF2 K48 poly‐ubiquitination. 32 Clearly, the upregulation of BAG6 greatly promoted BCL2 ubiquitination in MDA‐MB‐231 cells (Figure 6F ). A GST pull‐down assay in vitro was performed using the purified GST‐BAG6 and GST‐BCL2 proteins generated in E. coli BL21.…”
Section: Resultsmentioning
confidence: 91%
“…It was also involved in the regulation of apoptosis, antigen presentation and T‐cell response 30,31 . Furthermore, BAG6 could suppress RNA virus‐mediated innate immunity by increasing VISA/TRAF2 K48 poly‐ubiquitination 32 . Clearly, the upregulation of BAG6 greatly promoted BCL2 ubiquitination in MDA‐MB‐231 cells (Figure 6F).…”
Section: Resultsmentioning
confidence: 98%
“…Type I Interferon (IFN-I) plays a critical role in defending against viral infection and regulating innate immune response. A recent study reported that BAG6 was capable of regulating SeV-induced activation of IFN-I by inhibiting RIG-I/VISA-mediated innate immune response [ 29 ]. To assess the role of IFN-I pathway in BAG6-mediated anti-IAV response, we firstly examined the expressions of several key components involved in IFN-I signaling pathways, including pattern recognition receptor RIG-I, the phosphorylated STAT1 (P-STAT1) and the IFN-stimulated gene ISG15, in both BAG6 overexpressing and knocking-out HeLa cells during PR8 infection.…”
Section: Resultsmentioning
confidence: 99%
“…It promotes p53 transactivation by stabilizing its interaction with the acetyltransferase p300 and enhancing p53 acetylation during apoptosis and autophagy [ 21 , 22 , 53 ]. A recent study reported that BAG6 was capable of regulating the activation of IFN-I by inhibiting RIG-I/VISA-mediated recognition of RNA ligand [ 29 ]. However, the role of BAG6 in virus infection remains opaque.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of Bag6 in the lung is not yet fully understood, but there is evidence to suggest that it may play a role in regulating in ammation and immune responses in the lung. Bag6 appears to be a negative regulator in the innate immune system of non-small cell lung cancer patients [36] [37] and a risk factor for lung cancer [38] [39], even in early non-smoker lung adenocarcinoma patients [40]. Germline variants of genes involved in nuclear factor-kappa B (NF-κB) activation are associated with the risk of developing COPD and lung cancer [41].…”
Section: Discussionmentioning
confidence: 99%